Iron phosphate, lithium iron phosphate of gradient particle size, preparation method thereof and lithium ion battery

CN122355254BActive Publication Date: 2026-10-09JINCHI ENERGY MATERIALS CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610822678.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-09
Estimated Expiration
2046-06-09

AI Technical Summary

Technical Problem

然而,该方法依赖于研磨设备将物料粒度精准调控至百纳米级,对设备精度与工艺参数控制要求严苛;同时,其采用的二次烧结温度较高,易导致颗粒间发生熔融融合,损害材料的微观结构完整性,进而影响其电化学性能

Benefits of technology

本申请提供的梯度颗粒尺寸的磷酸铁的制备方法,采用一次颗粒可控化生产技术,可依据实际需求制备出不同纳米粒度的磷酸铁产品,磷酸铁合成过程中通过引入上一槽的晶种,所产出磷酸铁产品可在晶种尺寸基础上生长,进而生产出晶粒/颗粒尺寸递增的磷酸铁产品;另外,在生产制造中不同的晶粒/颗粒尺寸具有不同的适配温度,过烧会造成颗粒之间的熔融导致一次颗粒持续长大,不利于材料性能的提升以及成本方面的优化,另一方面采用后混批模式,根据磷酸铁锂前驱体不同尺寸特点,分别在磷酸铁煅烧端以及铁锂生产烧结端采用不同的烧结制度分开煅烧,可有效降低生产过程中能耗,增加盈利。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122355254B_ABST
    Figure CN122355254B_ABST
Patent Text Reader

Abstract

The application provides a gradient particle size iron phosphate, lithium iron phosphate and a preparation method thereof and a lithium ion battery, and relates to the field of lithium ion batteries. The preparation method of the iron phosphate comprises the following steps: mixing a ferrous salt solution, a phosphorus salt solution and an oxidizing agent, performing a coprecipitation reaction, and performing solid-liquid separation to obtain amorphous iron phosphate; performing slurry preparation on the amorphous iron phosphate to obtain a slurry; mixing the slurry and a phosphorus source to obtain a mixture A; performing aging and calcination on the mixture to obtain A-type iron phosphate; mixing the slurry, the phosphorus source and the A-type iron phosphate to obtain a mixture B; performing aging and calcination on the mixture B to obtain B-type iron phosphate; mixing the slurry, the phosphorus source and the B-type iron phosphate to obtain a mixture C; and performing aging and calcination on the mixture C to obtain C-type iron phosphate. In the synthesis process, the seed crystals of the previous tank are introduced, the produced iron phosphate can grow on the basis of the seed crystal size, and thus the iron phosphate with increasing crystal / grain size is produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion batteries, and more particularly to a gradient particle size of iron phosphate, lithium iron phosphate, its preparation method, and a lithium-ion battery. Background Technology

[0002] Lithium iron phosphate (LFP) materials possess advantages such as abundant raw material sources, non-toxicity, environmental friendliness, high safety, high specific capacity, stable cycle performance, and low cost, making them considered ideal cathode materials for lithium-ion batteries. However, their relatively low electronic conductivity and lithium-ion diffusion rate affect their electrochemical and low-temperature performance. Furthermore, the low tap density of LFP leads to a lower volumetric energy density, which also limits its further applications to some extent.

[0003] Currently, in the field of ferric phosphate preparation technology, researchers have developed various methods to achieve effective gradation of particles with different sizes. For example, patent text CN117163934A discloses a method for preparing two types of ferric phosphate using a co-precipitation method, where at least one is a doped ferric phosphate. This method utilizes the inhibitory effect of doped metal ions on the growth of ferric phosphate crystals to achieve gradation of ferric phosphate with different particle sizes. However, this technical solution requires a high degree of uniformity in the distribution of dopant elements in the ferric phosphate particles. In actual production, uneven doping can easily lead to particle size control failure, thus affecting the gradation effect and performance stability of the final product.

[0004] Patent CN120423517A discloses a multi-stage, high-pressure lithium iron phosphate preparation method. This method involves dispersing an iron source, phosphorus source, lithium source, carbon source a, dispersant, elemental dopant, and solvent in a specific ratio to prepare three slurries. These slurries are then spray-dried, pre-sintered, and ground to different particle sizes before undergoing further processing. middle Small particle gradation is followed by secondary sintering, pulverization, and demagnetization to produce high-pressure lithium iron phosphate cathode materials with multi-level gradation structures. However, this method relies on grinding equipment to precisely control the particle size to the hundred-nanometer level, which places stringent requirements on equipment precision and process parameter control. At the same time, the secondary sintering temperature used is relatively high, which can easily lead to melting and fusion between particles, damaging the integrity of the material's microstructure and thus affecting its electrochemical performance.

[0005] In summary, although various particle size distribution schemes for iron phosphate have been proposed in existing technologies, they all suffer from problems such as difficulty in process control, poor uniformity of particle size distribution, or easy damage to the microstructure during high-temperature treatment. These issues make it difficult to meet the requirements of high-performance lithium iron phosphate cathode materials for particle size gradient distribution and structural stability. Therefore, there is an urgent need to develop a method for preparing iron phosphate with gradient particle sizes to solve the aforementioned technical problems. Summary of the Invention

[0006] The purpose of this application is to provide a gradient particle size of iron phosphate, lithium iron phosphate, and their preparation methods, as well as a lithium-ion battery, to solve the above-mentioned problems.

[0007] To achieve the above objectives, the first aspect of this application provides a method for preparing iron phosphate with gradient particle sizes, comprising: Amorphous ferric phosphate was obtained by first mixing and coprecipitation of ferrous salt solution, phosphate solution and oxidant, followed by solid-liquid separation. The amorphous ferric phosphate is pulped to obtain a slurry; the slurry and a phosphorus source are mixed for a second time to obtain mixture A; the mixture is then aged and calcined for a first time to obtain type A ferric phosphate. The slurry, phosphorus source and type A ferric phosphate are mixed for a third time to obtain mixture B. Mixture B is then aged and calcined for a second time to obtain type B ferric phosphate. The slurry, phosphorus source and type B ferric phosphate are mixed for the fourth time to obtain mixture C. Mixture C is then aged and calcined for the third time to obtain type C ferric phosphate. The gradient particle size of ferric phosphate includes type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate.

[0008] Optionally, the molar concentration of the ferrous salt solution is 0.5-3 mol / L; And / or, the iron-to-phosphorus ratio in the coprecipitation reaction is 0.95-1.05:1; And / or, the oxidant includes one or more of oxygen, ozone, hydrogen peroxide, and ammonium persulfate; And / or, the coprecipitation reaction is carried out at a temperature of 30-80°C for a time of 0.5-5 hours.

[0009] Optionally, the pulping process includes: a fifth mixing of the amorphous ferric phosphate and water; And / or, the solid content of the slurry is 100-200 g / L; And / or, the concentration of the phosphorus source in each of the mixtures A, B and C is independently 10-30 mL / L; And / or, the first aging, the second aging, and the third aging each independently include sequential aging and heat preservation; the aging temperature is 30-80℃, and the time is 1-3h; the heat preservation temperature is 20-90℃, and the time is 0-6h; And / or, during the third mixing, the molar amount of iron in the type A ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry; And / or, during the fourth mixing, the molar amount of iron in the type B ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry.

[0010] Optionally, the first calcination temperature is 510-550℃ and the time is 1-3 hours; And / or, the second calcination temperature is 530-570℃, and the time is 1-3h; And / or, the third calcination temperature is 560-600℃, and the time is 1-3h.

[0011] The second aspect of this application provides a gradient particle size iron phosphate, which is prepared by the method for preparing gradient particle size iron phosphate.

[0012] Optionally, the particle size of type A ferric phosphate is 10-80 nm; And / or, the particle size of type B ferric phosphate is greater than 80 nm and less than 150 nm; And / or, the particle size of C-type ferric phosphate is ≥150nm.

[0013] The third aspect of this application discloses a method for preparing lithium iron phosphate, comprising: The type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate are respectively mixed with lithium source, carbon source, additive, water, and methanol to obtain mixed slurry A, mixed slurry B, and mixed slurry C. Under a protective atmosphere, the mixed slurry A is subjected to a first granulation and a fourth calcination to obtain type I lithium iron phosphate; Under a protective atmosphere, the mixed slurry B is subjected to a second granulation and a fifth calcination to obtain type II lithium iron phosphate; Under a protective atmosphere, the mixed slurry C is subjected to a third granulation and a sixth calcination to obtain type III lithium iron phosphate; The type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate are mixed in a seventh step to obtain lithium iron phosphate.

[0014] Optionally, the fourth calcination temperature is 730-770℃ and the time is 6-12h; And / or, the fifth calcination temperature is 760-800℃, and the time is 6-12h; And / or, the sixth calcination temperature is 780-820℃, and the time is 6-12h; And / or, the particle size of the type I lithium iron phosphate is <500 nm; And / or, the particle size of the type II lithium iron phosphate is 0.5-1.5 μm; And / or, the particle size of the type III lithium iron phosphate is >1.5 μm; And / or, during the seventh mixing, the mass ratio of the type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate is 60-75:15-30:5-15.

[0015] The fourth aspect of this application provides a lithium iron phosphate, which is prepared by the method for preparing lithium iron phosphate.

[0016] The fifth aspect of this application provides a lithium-ion battery, including the aforementioned lithium iron phosphate.

[0017] Compared with the prior art, the beneficial effects of this application include: The method for preparing graded particle size iron phosphate provided in this application employs a one-time controllable particle production technology, which can prepare iron phosphate products with different nanoparticle sizes according to actual needs. During the iron phosphate synthesis process, by introducing seed crystals from the previous tank, the produced iron phosphate products can grow based on the seed crystal size, thereby producing iron phosphate products with increasing grain / particle sizes. In addition, different grain / particle sizes have different suitable temperatures during production. Over-firing will cause melting between particles, leading to continuous growth of primary particles, which is not conducive to improving material performance and optimizing costs. On the other hand, by adopting a post-mixed batch mode, different sintering regimes are used separately at the iron phosphate calcination end and the lithium iron phosphate production sintering end according to the different size characteristics of the lithium iron phosphate precursor, which can effectively reduce energy consumption in the production process and increase profitability.

[0018] The gradient particle size iron phosphate provided in this application can be prepared with controllable nanoparticle size, which can achieve significant differences in particle size. After gradation, the filling layers between particles are higher, which improves the processing performance of the cathode material to a certain extent and increases the compaction density of the material.

[0019] The lithium iron phosphate preparation method provided in this application adopts a post-batch mixing mode to avoid changes in crystal / particle size due to overheating, which would increase the cost of lithium iron phosphate size gradation. This method enables controllable lithium iron phosphate nanoparticle size and guides the production of lithium iron phosphate materials with different performance characteristics according to different needs.

[0020] The lithium iron phosphate provided in this application has high compaction density and low cost.

[0021] The lithium-ion battery provided in this application has excellent electrochemical performance. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0023] Figure 1 The image shows a SEM image of lithium iron phosphate provided in Example 1. Detailed Implementation

[0024] First, the solution provided in this application will be explained in more detail as follows: The first aspect of this application provides a method for preparing iron phosphate with gradient particle sizes, comprising: Amorphous ferric phosphate was obtained by first mixing and coprecipitation of ferrous salt solution, phosphate solution and oxidant, followed by solid-liquid separation. The amorphous ferric phosphate is pulped to obtain a slurry; the slurry and a phosphorus source are mixed for a second time to obtain mixture A; the mixture is then aged and calcined for a first time to obtain type A ferric phosphate. The slurry, phosphorus source and type A ferric phosphate are mixed for a third time to obtain mixture B. Mixture B is then aged and calcined for a second time to obtain type B ferric phosphate. The slurry, phosphorus source and type B ferric phosphate are mixed for the fourth time to obtain mixture C. Mixture C is then aged and calcined for the third time to obtain type C ferric phosphate. It is important to note that type A iron phosphate has nanoscale primary particle size and uniform particle distribution. This invention utilizes the size inheritance of the seed crystal process, allowing the primary particle size of type B iron phosphate prepared using type A iron phosphate as a seed crystal to increase from the size of the type A seed crystal. Similarly, the primary particle size of type C iron phosphate prepared using type B iron phosphate as a seed crystal increases from the size of type B. This results in the production of three iron phosphate products with increasing grain / particle sizes, laying the foundation for the subsequent preparation of graded particle size lithium iron phosphate.

[0025] The gradient particle size of ferric phosphate includes type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate.

[0026] It is worth noting that this method can finely control the size of iron phosphate, and prepare corresponding gradient grain / particle sizes of lithium iron phosphate using iron phosphate with different grain / particle sizes as lithium iron phosphate precursors. Through the post-gradation method of lithium iron phosphate materials, high-compact lithium iron phosphate is produced. This method can achieve another breakthrough in optimizing compaction density and cost.

[0027] This application employs a controllable primary particle production technology for iron phosphate, which can prepare iron phosphate products with different nanoparticle sizes according to actual needs. The iron phosphate has strong controllability in size, high dispersibility between particles, and high reactivity.

[0028] In some embodiments, the molar concentration of the ferrous salt solution is 0.5-3 mol / L; Optionally, the molar concentration of the ferrous salt solution can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, or any value between 0.5 and 3 mol / L; And / or, the iron-to-phosphorus ratio in the coprecipitation reaction is 0.95-1.05:1; Optionally, the iron-to-phosphorus ratio in the coprecipitation reaction can be any value between 0.95:1, 1:1, 1.05:1, or 0.95:1. And / or, the oxidant includes one or more of oxygen, ozone, hydrogen peroxide, and ammonium persulfate; It should be noted that the addition of the oxidizing agent is to remove the Fe in the ferrous salt solution. 2+ Oxidized to Fe 3+ Thus, it reacts with PO4 in phosphate salts. 3- The reaction produces precipitates such as ferric phosphate; and / or the coprecipitation reaction is carried out at a temperature of 30-80°C for a time of 0.5-5 h.

[0029] Optionally, the temperature of the coprecipitation reaction can be any value between 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or 30-80℃, and the time can be any value between 0.5h, 1h, 2h, 3h, 4h, 5h or 0.5-5h.

[0030] In some embodiments, the pulping process includes: a fifth mixing of the amorphous ferric phosphate and water; And / or, the solid content of the slurry is 100-200 g / L; Optionally, the solid content of the slurry can be any value between 100 g / L, 150 g / L, 200 g / L, or 100-200 g / L; And / or, the concentration of the phosphorus source in each of the mixtures A, B and C is independently 10-30 mL / L; Optionally, the concentrations of the phosphorus source in mixtures A, B, and C can each be independently 10 mL / L, 15 mL / L, 20 mL / L, 25 mL / L, 30 mL / L, or any value between 10 and 30 mL / L; And / or, the first aging, the second aging, and the third aging each independently include sequential aging and heat preservation; the aging temperature is 30-80℃, and the time is 1-3h; the heat preservation temperature is 20-90℃, and the time is 0-6h; Optionally, the aging temperature can be any value between 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or 30-80℃, and the time can be any value between 1h, 2h, 3h or 1-3h; the heat preservation temperature can be any value between 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃ or 20-90℃, and the time can be any value between 0h, 1h, 2h, 3h, 4h, 5h, 6h or 0-6h. And / or, during the third mixing, the molar amount of iron in the type A ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry; Optionally, during the third mixing, the molar amount of iron in type A ferric phosphate accounts for any value between 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or 5-50% of the total molar amount of iron in the slurry. It is important to note that the dosage of type A ferric phosphate affects both production efficiency and the actual particle size of type B ferric phosphate. Higher dosage increases the input cost per batch of type B ferric phosphate, impacting production efficiency. Conversely, too low a dosage will fail to provide effective seeding, resulting in ferric phosphate that does not reflect the difference in primary particle size between the seed crystals and the finished product. And / or, during the fourth mixing, the molar amount of iron in the type B ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry.

[0031] Optionally, during the fourth mixing, the molar amount of iron in type B ferric phosphate accounts for any value between 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or 5-50% of the total molar amount of iron in the slurry.

[0032] It is important to note that the dosage of type B ferric phosphate is related to production efficiency and the actual particle size of type C ferric phosphate. Higher dosage increases the input cost per batch of type C ferric phosphate, while too low a dosage will not provide effective seeding, and the produced ferric phosphate will not reflect the difference in primary particle size between the seed crystal and the finished product.

[0033] In some embodiments, the temperature of the first calcination is 510-550°C, and the time is 1-3 hours; Optionally, the temperature of the first roasting can be any value between 510℃, 520℃, 530℃, 540℃, 550℃ or 510-550℃, and the time can be any value between 1h, 2h, 3h or 1-3h. And / or, the second calcination temperature is 530-570℃, and the time is 1-3h; Optionally, the temperature of the second roasting can be any value between 530℃, 540℃, 550℃, 560℃, 570℃ or 530-570℃, and the time can be any value between 1h, 2h, 3h or 1-3h. And / or, the third calcination temperature is 560-600℃, and the time is 1-3h.

[0034] Optionally, the temperature of the third roasting can be any value between 560℃, 570℃, 580℃, 590℃, 600℃ or 560-600℃, and the time can be any value between 1h, 2h, 3h or 1-3h. It is important to note that the calcination temperature ranges for the three types of ferric phosphate represent the optimal calcination temperatures for their specific primary particle sizes. Excessively high temperatures lead to excessive melting between particles, making it impossible to achieve controllable primary particle size production of the ferric phosphate material. Furthermore, excessively high temperatures are detrimental to the control of other indicators such as specific surface area. Conversely, excessively low calcination temperatures affect the crystal transformation process from dihydrate ferric phosphate to anhydrous ferric phosphate. At such low temperatures, the crystal transformation motive force is insufficient, and impurities such as sulfur cannot be effectively removed.

[0035] The second aspect of this application provides a gradient particle size iron phosphate, which is prepared by the method for preparing gradient particle size iron phosphate.

[0036] In some embodiments, the particle size of type A ferric phosphate is 10-80 nm; Optionally, the particle size of type A ferric phosphate can be any value between 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 10-80 nm; And / or, the particle size of type B ferric phosphate is greater than 80 nm and less than 150 nm; Optionally, the particle size of type B ferric phosphate can be any value between 85 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 145 nm, or greater than 80 nm and less than 150 nm. And / or, the particle size of C-type ferric phosphate is ≥150nm.

[0037] Optionally, the particle size of C-type iron phosphate can be any value of 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 250 nm or ≥150 nm.

[0038] The third aspect of this application discloses a method for preparing lithium iron phosphate, comprising: The type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate are respectively mixed with lithium source, carbon source, additive, water, and methanol to obtain mixed slurry A, mixed slurry B, and mixed slurry C. Under a protective atmosphere, the mixed slurry A is subjected to a first granulation and a fourth calcination to obtain type I lithium iron phosphate; Under a protective atmosphere, the mixed slurry B is subjected to a second granulation and a fifth calcination to obtain type II lithium iron phosphate; Under a protective atmosphere, the mixed slurry C is subjected to a third granulation and a sixth calcination to obtain type III lithium iron phosphate; The type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate are mixed in a seventh step to obtain lithium iron phosphate.

[0039] It is important to note that the calcination of iron phosphate and the sintering of lithium iron phosphate are carried out separately using different sintering regimes. This can effectively avoid melting between particles due to over-burning, thus preventing the material performance from being affected. On the other hand, separate calcination can reduce energy consumption during the production process and increase profitability. By adopting a post-mixing batch mode, it is possible to avoid changes in the grain / particle size of the product due to over-burning, which would increase the cost of lithium iron phosphate size gradation. This method enables controllable nanoparticle size of lithium iron phosphate and guides the production of lithium iron phosphate materials with different performance characteristics according to different needs.

[0040] In some embodiments, the fourth calcination temperature is 730-770°C and the time is 6-12 hours; Optionally, the temperature of the fourth roasting can be any value between 730℃, 740℃, 750℃, 760℃, 770℃ or 730-770℃, and the time can be any value between 6h, 7h, 8h, 9h, 10h, 11h, 12h or 6-12h. And / or, the fifth calcination temperature is 760-800℃, and the time is 6-12h; Optionally, the temperature of the fifth roasting can be any value between 760℃, 770℃, 780℃, 790℃, 800℃ or 760-800℃, and the time can be any value between 6h, 7h, 8h, 9h, 10h, 11h, 12h or 6-12h. And / or, the sixth calcination temperature is 780-820℃, and the time is 6-12h; Optionally, the temperature of the sixth roasting can be any value between 780℃, 790℃, 800℃, 810℃, 820℃ or 780-820℃, and the time can be any value between 6h, 7h, 8h, 9h, 10h, 11h, 12h or 6-12h. It is important to note that, similar to lithium iron phosphate, the temperature ranges specified for the three lithium iron phosphate materials are related to their primary particle size. Over-firing leads to structural collapse of the material, causing melting between small particles and resulting in increased size, which is detrimental to the subsequent directional gradation process. Over-firing also affects the material's capacity. Conversely, excessively low firing temperatures affect the solid-state reaction process, leading to incomplete reactions, a higher proportion of impurities in the phase structure, incomplete grain development, poor crystallinity, and directly reduced electrical performance. And / or, the particle size of the type I lithium iron phosphate is <500 nm; Optionally, the particle size of lithium iron phosphate type I can be any value of 100nm, 200nm, 300nm, 400nm, 490nm or <500nm; And / or, the particle size of the type II lithium iron phosphate is 0.5-1.5 μm; Optionally, the particle size of lithium iron phosphate type II can be 0.5 μm, 1 μm, 1.5 μm or any value between 0.5 and 1.5 μm; And / or, the particle size of the type III lithium iron phosphate is >1.5 μm; Optionally, the particle size of lithium iron phosphate type III can be any value of 1.6 μm, 2 μm, 2.5 μm, 3 μm or >1.5 μm; And / or, during the seventh mixing, the mass ratio of the type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate is 60-75:15-30:5-15.

[0041] Optionally, during the seventh mixing, the mass ratio of lithium iron phosphate type I, lithium iron phosphate type II, and lithium iron phosphate type III can be any value between (60:30:10), (65:20:20), (70:15:15), (75:15:10), (75:20:5), or 60-75:15-30:5-15.

[0042] It is important to note that the ratio of the three types of lithium iron phosphate allows for the construction of a framework with large and medium particles, while small particles fill the voids, forming a densely packed structure. This achieves the desired high compaction performance of the material, resulting in a compaction density > 2.72 g / cm³. 3 At the same time, a certain proportion of small particles are retained to maintain a good ionic / electronic conductivity network and electrochemical reversibility.

[0043] The fourth aspect of this application provides a lithium iron phosphate, which is prepared by the method for preparing lithium iron phosphate.

[0044] The fifth aspect of this application provides a lithium-ion battery, including the aforementioned lithium iron phosphate.

[0045] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0046] Example 1 The first aspect of this embodiment provides a gradient particle size iron phosphate and its preparation method, specifically as follows: S1: A co-precipitation method was used to prepare an iron salt solution with battery-grade ferrous sulfate as the iron source. The iron salt molar concentration was 0.5 mol / L and the iron-to-phosphorus ratio was 0.98:1. Then, a phosphate salt solution prepared with monoammonium phosphate and hydrogen peroxide were added and fed in parallel. The mixture was stirred at 30°C for 0.5 h. After the reaction was completed, the mixture was filtered and washed to obtain amorphous iron phosphate. S2: Add pure water to the above amorphous ferric phosphate to make a slurry, control the solid content of the slurry to 100g / L, then add phosphoric acid, the amount of phosphoric acid added is controlled to 10mL / L of slurry, age at 80℃ for 2h, then keep at 90℃ for 2h, and then calcine at 530℃ for 2h to obtain type A ferric phosphate. S3: Then, type A ferric phosphate (the molar amount of iron in type A ferric phosphate accounts for 5% of the total molar amount of iron in the slurry) is introduced into the pulp obtained in the pulping stage of the above steps, and the above aging and heat preservation processes are repeated, and then roasted at a temperature of 550℃ for 2 hours to obtain type B ferric phosphate. S4: Introduce type B ferric phosphate (the molar amount of iron in type B ferric phosphate accounts for 5% of the total molar amount of iron in the slurry) into the slurry obtained in the pulping stage above, repeat the above aging and heat preservation process, and then calcine it at a temperature of 580℃ for 2 hours to obtain type C ferric phosphate.

[0047] Among them, the average particle size of type A ferric phosphate is 50 nm; the average particle size of type B ferric phosphate is 100 nm; and the average particle size of type C ferric phosphate is 150 nm.

[0048] The second aspect of this embodiment provides a lithium iron phosphate and its preparation method, specifically as follows: S5: Type A lithium iron phosphate, lithium carbonate (Li to Fe molar ratio of 1.05:1), titanium dioxide (added at 3000 ppm based on Ti), 8% sucrose relative to the mass of lithium iron phosphate, and 6% PEG are mixed in pure water to obtain mixed slurry A. Mixed slurry A is granulated using a spray granulation device to obtain a dry powder material. Under nitrogen protection, the above powder material is sintered in a kiln at a sintering temperature of 750℃ for 6 hours. After cooling in the furnace, the sintered material is obtained. The sintered material is crushed, graded, and sieved to obtain type I lithium iron phosphate material.

[0049] S6: Using the same preparation method as S5, type A iron phosphate was replaced with type B iron phosphate, the sintering temperature was adjusted to 780℃ and the time was 6h to prepare type II lithium iron phosphate. S7: Using the same preparation method as S5, type A iron phosphate was replaced with type C iron phosphate, the sintering temperature was adjusted to 800℃ and the time was 6h to prepare type III lithium iron phosphate. S8: Type I lithium iron phosphate, Type II lithium iron phosphate and Type III lithium iron phosphate are graded in a mass ratio of 60%:30%:10% to obtain lithium iron phosphate.

[0050] Among them, the average particle size of type I lithium iron phosphate is 400 nm; the average particle size of type II lithium iron phosphate is 1 μm; and the average particle size of type III lithium iron phosphate is 3 μm.

[0051] SEM images of the lithium iron phosphate are as follows: Figure 1 As shown.

[0052] Example 2 The first aspect of this embodiment provides a gradient particle size iron phosphate and its preparation method, specifically as follows: S1: A co-precipitation method was used to prepare an iron salt solution with battery-grade ferrous sulfate as the iron source. The iron salt molar concentration was 1 mol / L and the iron-to-phosphorus ratio was 0.98:1. Then, a phosphate salt solution prepared with monoammonium phosphate and hydrogen peroxide were added and fed in parallel. The mixture was stirred at 30°C for 0.5 h. After the reaction was completed, the mixture was filtered and washed to obtain amorphous iron phosphate. S2: Add pure water to the above amorphous ferric phosphate to make a slurry, control the solid content of the slurry to 200g / L, then add phosphoric acid, the amount of phosphoric acid added is controlled to 10mL / L of slurry, age at 50℃ for 2h, then keep at 90℃ for 2h, and then calcine at 520℃ for 2h to obtain type A ferric phosphate. S3: Then, type A ferric phosphate (the molar amount of iron in type A ferric phosphate accounts for 5% of the total molar amount of iron in the slurry) is introduced into the pulp obtained in the pulping stage of the above steps, and the above aging and heat preservation processes are repeated, and then roasted at a temperature of 540℃ for 2 hours to obtain type B ferric phosphate. S4: Introduce type B ferric phosphate (the molar amount of iron in type B ferric phosphate accounts for 5% of the total molar amount of iron in the slurry) into the slurry obtained in the pulping stage above, repeat the above aging and heat preservation process, and then calcine it at a temperature of 570℃ for 2 hours to obtain type C ferric phosphate.

[0053] Among them, the average particle size of type A ferric phosphate is 70 nm; the average particle size of type B ferric phosphate is 120 nm; and the particle size of type C ferric phosphate is 180 nm.

[0054] The second aspect of this embodiment provides a lithium iron phosphate and its preparation method, specifically as follows: S5: Type A lithium iron phosphate, lithium carbonate (Li to Fe molar ratio of 1.05:1), titanium dioxide (added at 3000 ppm based on Ti), 8% sucrose relative to the mass of lithium iron phosphate, and 6% PEG are mixed in pure water to obtain mixed slurry A. Mixed slurry A is granulated using a spray granulation device to obtain a dry powder material. Under nitrogen protection, the above powder material is sintered in a kiln at a sintering temperature of 750℃ for 6 hours. After cooling in the furnace, the sintered material is obtained. The sintered material is crushed, graded, and sieved to obtain type I lithium iron phosphate material.

[0055] S6: Using the same preparation method as S5, type A iron phosphate was replaced with type B iron phosphate, the sintering temperature was adjusted to 780℃ and the time was 6h to prepare type II lithium iron phosphate. S7: Using the same preparation method as S5, type A iron phosphate was replaced with type C iron phosphate, the sintering temperature was adjusted to 800℃ and the time was 6h to prepare type III lithium iron phosphate. S8: Type I lithium iron phosphate, Type II lithium iron phosphate and Type III lithium iron phosphate are graded in a mass ratio of 60%:25%:15% to obtain lithium iron phosphate.

[0056] Among them, the average particle size of type I lithium iron phosphate is 300 nm; the average particle size of type II lithium iron phosphate is 1 μm; and the average particle size of type III lithium iron phosphate is 3 μm.

[0057] Example 3 The first aspect of this embodiment provides a gradient particle size iron phosphate and its preparation method, specifically as follows: S1: A co-precipitation method was used to prepare an iron salt solution with battery-grade ferrous sulfate as the iron source and the iron salt molar concentration of 0.8 mol / L. The iron-to-phosphorus ratio was 0.98:1. Then, a phosphate salt solution prepared with monoammonium phosphate and hydrogen peroxide were added and fed in parallel. The mixture was stirred at 30°C for 1 hour. After the reaction was completed, the mixture was filtered and washed to obtain amorphous iron phosphate. S2: Add pure water to the above amorphous ferric phosphate to make a slurry, control the solid content of the slurry to 150 g / L, then add phosphoric acid, the amount of phosphoric acid added is controlled to 10 mL / L of slurry, age at 80℃ for 2 h, then keep at 90℃ for 2 h, and then calcine at 530℃ for 2 h to obtain type A ferric phosphate. S3: Then, type A ferric phosphate (the molar amount of iron in type A ferric phosphate accounts for 10% of the total molar amount of iron in the slurry) is introduced into the slurry obtained in the pulping stage of the above steps, and the above aging and heat preservation processes are repeated, and then calcined at a temperature of 550℃ for 2 hours to obtain type B ferric phosphate. S4: Introduce type B ferric phosphate (the molar amount of iron in type B ferric phosphate accounts for 10% of the total molar amount of iron in the slurry) into the slurry obtained in the pulping stage above, repeat the above aging and heat preservation process, and then calcine it at a temperature of 580℃ for 2 hours to obtain type C ferric phosphate.

[0058] Among them, the average particle size of type A ferric phosphate is 70 nm; the average particle size of type B ferric phosphate is 100 nm; and the average particle size of type C ferric phosphate is 250 nm.

[0059] The second aspect of this embodiment provides a lithium iron phosphate and its preparation method, specifically as follows: S5: Type A lithium iron phosphate, lithium carbonate (Li to Fe molar ratio of 1.05:1), titanium dioxide (added at 3000 ppm based on Ti), 8% sucrose relative to the mass of lithium iron phosphate, and 6% PEG are mixed in pure water to obtain mixed slurry A. Mixed slurry A is granulated using a spray granulation device to obtain a dry powder material. Under nitrogen protection, the above powder material is sintered in a kiln at a sintering temperature of 750℃ for 6 hours. After cooling in the furnace, the sintered material is obtained. The sintered material is crushed, graded, and sieved to obtain type I lithium iron phosphate material.

[0060] S6: Using the same preparation method as S5, type A iron phosphate was replaced with type B iron phosphate, the sintering temperature was adjusted to 780℃ and the time was 6h to prepare type II lithium iron phosphate. S7: Using the same preparation method as S5, type A iron phosphate was replaced with type C iron phosphate, the sintering temperature was adjusted to 800℃ and the time was 6h to prepare type III lithium iron phosphate. S8: Type I lithium iron phosphate, Type II lithium iron phosphate and Type III lithium iron phosphate are graded in a mass ratio of 60%:30%:10% to obtain lithium iron phosphate.

[0061] Among them, the average particle size of type I lithium iron phosphate is 1500 nm; the average particle size of type II lithium iron phosphate is 0.75 μm; and the average particle size of type III lithium iron phosphate is 2.5 μm.

[0062] Comparative Example 1 The difference from Example 1 is that only type A iron phosphate was prepared, and type I lithium iron phosphate material was subsequently prepared according to step S5.

[0063] Comparative Example 2 The difference from Example 1 is that the calcination temperature was 580°C when preparing type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate.

[0064] Comparative Example 3 The difference from Example 1 is that the calcination temperature was 800°C when preparing type I lithium iron phosphate, type II lithium iron phosphate and type III lithium iron phosphate.

[0065] Comparative Example 4 The difference from Example 1 is that phosphoric acid is not added during the aging process in steps S2, S3 and S4.

[0066] Comparative Example 5 The difference from Example 1 is that ferric phosphate A is not added during the roasting in step S3.

[0067] Comparative Example 6 The difference from Example 1 is that ferric phosphate B is not added during the calcination of step S4.

[0068] Comparative Example 7 The difference from Example 1 is that in step S5, type A iron phosphate is replaced with a mixture of type A iron phosphate, type B iron phosphate and type C iron phosphate, and the subsequent steps S6, S7 and S8 are not performed; that is, this comparative example does not prepare type I lithium iron phosphate, type II lithium iron phosphate and type III lithium iron phosphate separately, but uses a mixture of iron phosphate with gradient particle sizes for one-step preparation.

[0069] Example 1 3. Comparative Example 1 The lithium iron phosphate prepared in 7 was used as the positive electrode material for lithium batteries. The lithium iron phosphate material was mixed with conductive carbon material and polyvinylidene chloride binder in a mass ratio of 90:5:5, and N was added dropwise. Methylpyrrolidone was ground into a paste and coated onto the surface of aluminum foil. After drying at 120°C, it was cut into sheets and then seamlessly rolled to obtain the positive electrode test electrode. The loading of active material on the positive electrode sheet was controlled at 9-10 mg, and the compaction density of the electrode sheet was controlled at 2.35-2.40 g / cm³. 2The coin cell model is CR2032. The counter electrode (reference electrode) is a lithium metal sheet, and the electrolyte is a product of Shenzhen Capchem Technology Co., Ltd. The coin cells were assembled in a glove box with controlled moisture and oxygen levels. They were then placed in a 25°C constant temperature chamber for 24 hours before being connected to a blue-chip battery tester for charge-discharge testing. The coin cells were placed in a 25°C constant temperature chamber for charge-discharge testing. The nominal capacity at 1C was set at 170mAh / g. Within the range of 2.0-3.75V, the cells were first activated at 0.1C for one week, then charged and discharged at 1.0C. The constant voltage cutoff current at 3.75V was 0.02C, and the charge-discharge curves were observed.

[0070] Charge and discharge performance tests were conducted, and the test results are shown in Table 1.

[0071] Table 1 Electrochemical Performance Tests

[0072] analyze: The tests above show that the compaction of the lithium iron phosphate cathode material prepared in the examples is higher than 2.72 g / cm³. 3 It was significantly better than the comparative example (2.14-2.58 g / cm³). 3 This is because the embodiments employ a particle size gradation technology, which effectively improves the compaction of the material and achieves the purpose of high compaction. Comparative Example 1's product only contains small-particle lithium iron phosphate, without large-particle lithium iron phosphate to support high compaction, thus exhibiting a lower material compaction density. The particle size of the lithium iron phosphate material does not affect the electrochemical performance. In Comparative Example 2, due to excessively high temperature during the dehydration process of iron phosphate, more material melts, resulting in an increase in large particles and uncontrollable size, thereby affecting the compaction of the cathode material. The electrical performance data shows that larger iron phosphate particles negatively impact the material's electrical properties. In Comparative Example 3, the excessively high temperature during lithium iron phosphate sintering led to an increase in large particles and reduced compaction. Over-burning also negatively affected electrical performance. In Comparative Example 4, considering both compaction and electrical performance data, the absence of phosphoric acid during aging prevented amorphous iron phosphate from transforming into crystals, hindering the development of seed crystals and controllable particle size. Consequently, the material exhibited low compaction and electrical performance. In Comparative Examples 5 and 6, the lack of gradient preparation of iron phosphate size reduced the material's compaction level to some extent, but the electrical performance remained largely unchanged. In Comparative Example 7, prioritizing particle size distribution of iron phosphate before uniform preparation into lithium iron phosphate cathode material resulted in a slight decrease in compaction. This indicates that the mixed batch of iron phosphate inevitably experienced melting of small particles during lithium iron phosphate sintering, reducing the cathode material's particle size distribution and consequently affecting compaction.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0074] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing iron phosphate with gradient particle sizes, characterized in that, include: Amorphous ferric phosphate was obtained by first mixing and coprecipitation of ferrous salt solution, phosphate solution and oxidant, followed by solid-liquid separation. The amorphous ferric phosphate was pulped to obtain a slurry; The slurry and phosphorus source are mixed for the second time to obtain mixture A. The mixture is then subjected to a first aging and a first calcination to obtain type A ferric phosphate. The slurry, phosphorus source and type A ferric phosphate are mixed for a third time to obtain mixture B. Mixture B is then aged and calcined for a second time to obtain type B ferric phosphate. The slurry, phosphorus source and type B ferric phosphate are mixed for the fourth time to obtain mixture C. Mixture C is then aged and calcined for the third time to obtain type C ferric phosphate. The gradient particle size of ferric phosphate includes type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate; The first calcination temperature is 510-550℃, and the time is 1-3 hours; The second roasting temperature is 530-570℃, and the time is 1-3 hours; The third roasting temperature is 560-600℃, and the time is 1-3 hours; The first aging, the second aging, and the third aging each independently include sequential aging and heat preservation; the aging temperature is 30-80℃ and the time is 1-3 hours; the heat preservation temperature is 20-90℃ and the time is 0-6 hours. The particle size of the type A ferric phosphate is 10-80 nm; The particle size of the type B ferric phosphate is greater than 80 nm and less than 150 nm; The particle size of the C-type iron phosphate is ≥150nm.

2. The method for preparing graded particle size iron phosphate according to claim 1, characterized in that, The molar concentration of the ferrous salt solution is 0.5-3 mol / L; And / or, the iron-to-phosphorus ratio in the coprecipitation reaction is 0.95-1.05:1; And / or, the oxidant includes one or more of oxygen, ozone, hydrogen peroxide, and ammonium persulfate; And / or, the coprecipitation reaction is carried out at a temperature of 30-80°C for a time of 0.5-5 hours.

3. The method for preparing graded particle size iron phosphate according to claim 1, characterized in that, The pulping process includes: a fifth mixing of the amorphous ferric phosphate and water; And / or, the solid content of the slurry is 100-200 g / L; And / or, the concentration of the phosphorus source in each of the mixtures A, B and C is independently 10-30 mL / L; And / or, during the third mixing, the molar amount of iron in the type A ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry; And / or, during the fourth mixing, the molar amount of iron in the type B ferric phosphate accounts for 5%-50% of the total molar amount of iron in the slurry.

4. A gradient particle size iron phosphate, characterized in that, It is prepared by the method for preparing gradient particle size iron phosphate according to any one of claims 1-3.

5. A method for preparing lithium iron phosphate, characterized in that, include: The type A ferric phosphate, type B ferric phosphate, and type C ferric phosphate described in any one of claims 1-3 are respectively mixed with a lithium source, a carbon source, an additive, water, and methanol to obtain mixed slurry A, mixed slurry B, and mixed slurry C, respectively. Under a protective atmosphere, the mixed slurry A is subjected to a first granulation and a fourth calcination to obtain type I lithium iron phosphate; Under a protective atmosphere, the mixed slurry B is subjected to a second granulation and a fifth calcination to obtain type II lithium iron phosphate; Under a protective atmosphere, the mixed slurry C is subjected to a third granulation and a sixth calcination to obtain type III lithium iron phosphate; The type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate are mixed in a seventh step to obtain lithium iron phosphate; The fourth roasting temperature is 730-770℃, and the time is 6-12h; The fifth roasting temperature is 760-800℃, and the time is 6-12h; The sixth roasting temperature is 780-820℃, and the time is 6-12h; The particle size of the type I lithium iron phosphate is <500nm; The type II lithium iron phosphate has a particle size of 0.5-1.5 μm; The particle size of the type III lithium iron phosphate is >1.5μm; During the seventh mixing process, the mass ratio of the type I lithium iron phosphate, the type II lithium iron phosphate, and the type III lithium iron phosphate is 60-75:15-30:5-15.

6. A lithium iron phosphate, characterized in that, It is prepared by the method for preparing lithium iron phosphate as described in claim 5.

7. A lithium-ion battery, characterized in that, Including the lithium iron phosphate as described in claim 6.

Citation Information

Patent Citations

  • Iron phosphate grading type lithium iron phosphate material and preparation method thereof

    CN117163934A

  • Preparation method of multi-stage grading high-compaction lithium iron phosphate

    CN120423517A

  • Preparation method of iron phosphate

    CN115403019A

  • Lithium iron phosphate positive electrode material, preparation method thereof and lithium battery

    CN119612474A

  • Preparation method of grain size grading iron phosphate and high compaction type lithium iron phosphate

    CN121202088A